Upravljanje rizikom prinosa u obveznim kapitalno financiranim mirovinskim sustavima - Potočnjak, Željko, pravnik (Array, 2008)
The introduction of pension systems of individual capitalized saving inspired an extensive debate on how to protect insured persons from different risks associated with the capital market. In the last few months, these issues have been made particularly relevant because of signifi cant negative trends on the world capital markets, but also because of a large drop of the value of the assets that are traded on the Zagreb market, and in which Croatian pension funds are investing. The authors pay a special attention to the risk of returns, as they consider it to be the most important risk on which the level of pensions of the insured persons from the compulsory capital fi nanced part of the pension system will largely depend. Differences in returns are possible not only in relation to the successfulness of the operation of the selected pension fund, but also considering the choice of the day on which the assets accumulated on the insured person's saving account will be transferred to the pension insurance company responsible for the payment of pensions. Therefore the modalities of risk management of returns are analysed from the theoretical and comparative standpoints, presenting the manners of protecting the assets of pension funds from the risk of negative or insuffi cient returns. The aforementioned issues are important in Croatia for the successfulness of the implementation of the project of multipillar pension system, in which one part is fi nanced from the capital, and thus also for the social security of the citizens who will realise pensions from that system. These issues are important for understanding different challenges that capital fi nanced systems are faced with, unlike pay-asyou- go pension systems